The Zoomers' handbook - Moraes, Ana de, 1978-; Moraes, Thiago de, 1977- (2016)
Aspiring Zoomers, who look after very special beasts, discover the secret of the shiger's stripy wool, the challenges of owning a loyal but gigantic dogephant, and the special skills of the super-fast horsodile.
"First published in 2015 by Andersen Press Ltd, London"--Title page verso.
Keywords: Imaginary creatures -- Fiction; Humorous stories